Requirements Elicitation in Software Engineering - Ali Ramdhani, Muhammad; Sa’adillah Maylawati, Dian; Syakur Amin, Abdusy; Aulawi, Hilmi (International Journal of Engineering and Technology, 2018)
Software Engineering (SE) is a discipline, concept, method that focus on all aspects related to software production. SE must adapt organized system and approach in building software. The objective of this article is to discuss needs elicitation in SE, so that the design can be done through utilizing appropriate tools and techniques based on the problem to be solved, restrictions and need that must be met, as well as resource availability. The method used in this article is literature review as a major source of problem analysis. In the next phase, the main topic of the article is clarified, validated, and verified by the model of the Focus Group Discussion (FGD). The respondents of FGD are lecturers of Informatics Department at UIN Sunan Gunung Djati Bandung. Requirements elicitation is in-dept and comprehensive process of finding information from all stakeholders in relation to the built software. The result of requirements elicitation is the explanation from every stakeholder with natural language related to the will and interest of the built software. The mechanism of finding information can be done through observation, questionnaire, interview, and documentary study, which are then tested with data validation and verification in FGD. The product of requirements elicitation is the User Requirement Document (URD) that can be used as an early artifact in software development process. Furthermore, URD is used as a reference in tracking the suitability between the function of software and the needs of stakeholder. This article formulated analysis approach of SE need, so that it is easily modified, adaptive to growing software complexity, and connected with the analysis of hardware.Â